'My children are small and my husband works far from home': juggling land and labour in a Vietnamese village. (2nd July 2020) - Nguyen, Tuan Anh; Rigg, Jonathan; Derks, Annuska
Abstract : This paper explores the links between migration and changes in household agricultural production in Vietnam during the reform period (1986–2012) through a case study of Quỳnh Đôi village, Nghệ An Province. Since reforms were first introduced, many villagers have left Quỳnh Đôi to work in cities, industrial zones or to find employment abroad. The migration process has transformed labour structures and supply, leading to changes in household agricultural production across two dimensions. First, renting or exchanging agricultural land has become common between households in Quỳnh Đôi, and between Quỳnh Đôi villagers and a neighbouring commune. This renting/exchanging of agricultural land has helped redistribute land among households that would otherwise be rich in land and poor in labour, or vice versa. These transactions have not been purely market-based but carried out mainly through verbal agreements dependent on networks of social capital and trust. Second, because many farm labourers have migrated, households require additional human labour for agricultural production. Facing this situation, various forms of labour exchange have emerged. Migration has, therefore, become an important generator of change in farming.